Does a rabbit have feathers or fur? Development of a 42-item semantic memory test (SMT-42) - Mazoué, Aurélien; Gaultier, Aurélie; Rocher, Laëtitia; Deruet, Anne-Laure; Vercelletto, Martine; Boutoleau-Bretonnière, Claire (Journal of clinical and experimental neuropsychology, 2022)
We present the preliminary study of the 42-item Semantic Memory Test (SMT-42), a test developed to distinguish semantic variant primary progressive aphasia (svPPA) from the other variants: logopenic (lPPA) and nonfluent/agrammatic (naPPA). The test requires the patient to retrieve the conceptual features of items belonging to different lexical categories. In the first study, we administered the French version of the SMT-42 to a population of healthy subjects and to patients with svPPA matched to a subgroup of the healthy subjects. In the second study, we administered the SMT-42 to four groups of patients (with svPPA, lPPA, naPPA and Alzheimer's disease [AD], respectively) to study its capacity to differentiate patients suffering from svPPA from the other patients. In the first study, 109 healthy subjects were included, 15 of whom were paired with 15 subjects presenting with svPPA. In the second study, designed to compare groups presenting a primary progressive aphasia variant and AD, 12 subjects with svPPA, 6 with naPPA and 9 with lPPA were included, along with 21 subjects with AD. The subjects presenting a semantic deficit were clearly distinguished from the others by their results on the SMT-42 (svPPA: mean = 30.0 (5.9); lPPA: mean = 37.8 (3.3), d = 1.5, p = 0.002; naPPA: mean = 39.8 (1.9), d = 1.89, p = 0.001; AD: mean = 38.5 (2.4), d = 1.63, p < 0.001); (svPPA: median = 31; lPPA: median = 38, U = 9, p = 0.002; naPPA: median = 40.5, U = 1.5, p = 0.001; AD: median = 39, U = 13.5, p < 0.001). The SMT-42 is simple, rapidly administered (3 minutes on average), easily scored and has good sensitivity, and it appears to be an effective tool for semantic screening in routine clinical practice.